Helpdesk Ticketing Information System Based on Android at Communication and Information Department of Badung Regency - Damayanti, Dewi Ayu Sulistyo; Suyadnya, I Made Arsa; Khrisne, Duman Care (Journal of Electrical, Electronics and Informatics; Vol 5 No 2 (2021): JEEI (September 2021)DO - 10.24843/JEEI.2021.v05.i02.p01, 2021)
In the operational activities of Diskominfo at Badung Regency, there are often reports of service problems every day. Currently, the reporting of these problems is still done in person via telephone or short message, which affects the speed of handling the report. The complaint system is a solution to problems related to reporting and handling of these service problems. In this study, a mobile application-based complaint system will be developed for the client-side to make it easier for clients to report or respond to reports and for the server-side, it will be developed on a web-based basis to still facilitate the management of complaint data. This study uses Data Flow Diagrams to model the process and Entity Relationship Diagrams to model its database. The evaluation process is carried out using the black box testing method and usability evaluation using SEQ and SUS. The system that has been successfully developed is able to carry out the main processes related to adding reports, viewing report progress, verifying reports, following up on reports, and changing report status. Testing using the black box testing method on 7 test classes with 74 test scenarios to get 74 valid test scenarios. Testing the installation and use of applications on 3 types of smartphones has also been successfully carried out without any problems. Usability testing on users using SEQ gets a middle value of 6 (for Administrator and IT Staff) and 7 (for Verification), which shows that the application developed is easy to use by the user, with the results of the SUS the questionnaire, the user shows that the application is in the Excellent class with an average value obtained from 15 respondents of 80.5.